Effectiveness of Cleaning Liquid on the Internal Quality of Chicken Egg During Storage - Riyanti Riyanti; Dani Prabowo; Khaira Nova; Dian Septinova (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2022)
This research aimed to determine the effect of cleaning liquid, storage duration, and the type of the best cleaning liquid and storage duration on the albumen index, yolk index, and haugh unit of chicken egg. This research was conducted from 21 January–10 February 2022 at the Livestock Production Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. This research was conducted using a completely randomized design with a nested pattern with cleaning liquid (control, water, warm water, and alcohol 70%) as the main plot and long storage (7, 14, and 21 days) as subplots. Each treatment was repeated 3 times and each replication used 3 eggs, so that the total eggs used were 108 eggs with average egg weight of 59,71±6,33 and coefficient of diversity of 4,58%. The observed variables included albumen index, yolk index, and haugh unit (HU). The research data were analyzed with analysis of variance at the 5% level, if significantly different, continued with the BNT test. The results of the albumen index, yolk index, and haugh unit showed that the cleaning liquid treatment had no significant effect (P>0,05), while the storage duration treatment had a significant effect (P<0,05). Storage duration of 7 days can maintain albumen index, yolk index, and haugh unit from all treatments. The conclusion was the cleaning liquid and the best storage duration were alcohol 70% and 7 days of storage.